The Contribution of International Trade to Economic Growth and Productivity - Puspitasari, Riska; Arif , Zia Ullah; Sari, Maya Inayati; Ahmed, Ali M. (Zabags International Journal of Economy, 2024)
This study examines the role of international trade in driving economic growth and development, particularly in emerging countries. Economic growth has long been considered a central indicator of national progress, though it is also interconnected with issues such as poverty, unemployment, inflation, and income inequality. International trade through exports and imports serves as a key catalyst for expansion by stimulating specialization, generating investible surplus, enabling vent-for-surplus opportunities, and increasing overall productivity. Using an experimental research approach, this study evaluates the impact of trade on domestic production, highlighting that globalization, technological transfer, and economies of scale significantly contribute to growth. Findings show that international trade not only provides access to scarce goods and broader markets but also facilitates knowledge and technology transfer, which enhances efficiency and competitiveness. However, challenges remain in ensuring equitable distribution of trade benefits, preparedness of local industries to absorb new technologies, and the willingness of developed countries to share innovation. Thus, while international trade accelerates growth, its effectiveness depends on domestic policies and the appropriateness of transferred technologies for developing nations’ needs.